TCP SYN flood attack analysis based on payload - Siti Hajar, C. Haris; R. Badlishah, Ahmad, Prof. Madya Dr.; Mohd Alif Hasmani, Abd Ghani; Che Muhammad Nor, Che Isa (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.